The Mangrove Density, Diversity, and Environmental Factors as Important Variables to Support the Conservation Program of Essential Ecosystem Area in Muara Kali Ijo, Pantai Ayah, Kebumen - Sri Murniasih; Eko Hendarto; Endang Hilmi (Jurnal Sylva Lestari, 2022)
The planning of wetland essential ecosystem area (EEA) conservation and preservation activities is important to support ecosystem stability, including the mangrove ecosystem. These activities should consider the ecological, economic, and social aspects. This study aimed to analyze the indicator of the mangrove ecosystem to support the planning program of EEA conservation in Muara Kali Ijo, Pantai Ayah, Kebumen. The research method used the mapping and planning analysis of the EEA conservation program using the indicator of mangrove density, mangrove diversity, and environmental indicators. The results showed that mangrove density in Muara Kali Ijo was 1,500-4,300 trees/ha (moderate to very dense) and was dominated by Rhizophora mucronata and Rhizophora styllosa. The potential of total dissolved solids, water salinity, potential hydrogen, dissolved oxygen, biological oxygen demand, and nitrate had a good condition to support the mangrove's life and growth. The ecosystem essential planning also had activity to conserve and preserve the Crocodylus porosus. The planning of ecosystem essential was developed in 18.5 ha, divided into five zones: mangrove preservation area of 5.90 ha, mangrove utilization area of 6.40 ha, mangrove arboretum of 4.40 ha, mangrove rehabilitation area of 1.30 ha, and specific utilization area of 0.5 ha. The wetland EEA in Muara Kali Ijo has important value in preserving the area from coastal disaster and increasing economic value with tourism and other activities. Keywords: Crocodylus porosus preservation, essential ecosystem conservation, mangrove zonation, Muara Kali Ijo, wetland conservation